EKSISTENSI TRADISI SAYYANG PATTUDU ATAU KUDA MENARI PADA SUKU MANDAR PROVINSI SULAWESI BARAT - Arifin, Ibrahim (DISCOURSE: Indonesian Journal of Social Studies and Education, 2023)
This study was conducted in the Polewali Mandar Regency in several sub-districts such as Tinambung District, Balanipa District, and Campalagian District, to study how the Sayyang Pattudu culture can still survive in the modern era, which is a cultural result of the Mandar community. Qualitative research approach using descriptive methods. Data collection through observation and document study and continued with descriptive analysis culture. Sayyang Pattuddu is a culture of the Mandar people which in ancient times was only practiced by the royal family. This culture is to give appreciation to children who have succesfully completed the Koran and then paraded around the village using dancing horses. However, even though this tradition and culture has been around for a long time, this culture is still very well preserved and exists today.